PENGARUH PEGGUNAAN E-COMMERCE TERHADAP KEPUTUSAN PEMBELIAN CUSTOMER DI RESTORAN PONDOK HARI HARI JAKARTA - Vanessa Aurelia; Prayogo Susanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of e-commerce usage on customer purchasing decisions at Pondok Hari-Hari Restaurant in Jakarta. The development of online food ordering applications such as GoFood, GrabFood, and ShopeeFood has changed consumer behavior in purchasing food products. Restaurants are not only required to provide good food quality but also need to manage good digital services. This study uses a quantitative approach with a questionnaire survey method. Data were collected through questionnaires from 99 respondents who have made online purchases at Pondok Hari-Hari Restaurant in Jakarta. Data analysis was conducted with the help of SPSS and includes validity tests that shows the results is higher than table r , reliability tests, normality tests, heteroscedasticity tests, simple linear regression tests, T-tests, F-tests, and determination coefficient tests. Reliability test results showed a Cronbach's alpha value of 0.963 for variable X and 0.891 for variable Y, which means all statement instruments are declared reliable. With a coefficient of determination value of 0.531, which indicates that the use of e-commerce contributes 53,1% to purchase decisions, while the remaining 46,9% is influenced by other factors not discussed in this study. Thus, the use of e- commerce is proven to have a positive and significant effect on customer purchase decisions at Pondok Hari-Hari Restaurant in Jakarta.